International Students’ Expectations and Perceptions of Service Quality: The Case of a Higher Education Institution in South Africa - Govender, Jeevarathnam P; ., Dion T Noel (Journal of Economics and Behavioral Studies, 2012)
South Africa has recently seen a significant increase in international student enrolments in recent years. In order to be competitive, attention needs to be given to service quality with a view to being the institution of preference. This paper therefore seeks to assess international students’ expectations and perceptions of service quality. A census was conducted among the 215 international students, using the SERVQUAL model as the measuring instrument. The results indicate that there are gaps between international students’ expectations and perceptions on the five service quality dimensions. An analysis of variance was conducted to test for significant differences between three biographical variables viz. faculty of study, qualification enrolled for and region of residence versus the five dimensions of service quality, on both expectations and perceptions. Recommendations are presented on how the institution can enhance service quality among its international students.